Implementasi Model Pembelajaran Berbasis Studi Kasus dalam Meningkatkan Pemahaman terhadap Hak dan Kewajiban Warga Negara pada Siswa Sekolah Dasar Negeri 101890 Dalu Sepuluh A - Nurbaiti Saringin; Nizmi Putri; Thessa Herdyana (Medan Resource Center, 2026)
Understanding citizens’ rights and responsibilities is a fundamental objective of citizenship education at the elementary school level. However, many students experience difficulties in comprehending and applying these concepts meaningfully due to the predominance of teacher-centered instructional approaches. This study aimed to examine the implementation of a case study-based learning model in improving students’ understanding of citizens’ rights and responsibilities at State Elementary School 101890 Dalu Sepuluh A. The research employed a Classroom Action Research design involving 26 elementary school students and was conducted through two action cycles consisting of planning, implementation, observation, and reflection stages. Data were collected through observation sheets and learning outcome assessments to evaluate students’ conceptual understanding. The findings indicated a substantial improvement in students’ mastery of the learning material following the implementation of the case study-based learning model. Students demonstrated greater engagement in classroom discussions, improved analytical skills in examining real-life civic issues, and a deeper understanding of the relationship between rights and responsibilities as citizens. The study concludes that the case study-based learning model is an effective instructional approach for enhancing students’ civic understanding by promoting active participation, critical thinking, and contextual learning experiences.